Influence of Belowground Herbivory on the Dynamics of Root and Rhizosphere Microbial Communities - Ourry, Morgane; Lebreton, Lionel; Chaminade, Valérie; Guillerm-Erckelboudt, Anne-Yvonne; Hervé, Maxime; Linglin, Juliette; Marnet, Nathalie; Ourry, Alain; Paty, Chrystelle; Poinsot, Denis; Cortesero, Anne-Marie; Mougel, Christophe (Frontiers in Ecology and Evolution, 2018)
Recent studies are unravelling the impact of microorganisms from the roots and rhizosphere on interactions between plants and herbivorous insects and are gradually changing our perception of the microorganisms’ capacity to affect plant defenses, but the reverse effect has seldom been investigated. Our study aimed at determining how plant herbivory influences the dynamics of root and rhizosphere microbial community assemblages and whether potential changes in root metabolites and chemical elements produced during herbivory can be related to microbial community diversity. We conducted our study on oilseed rape (Brassica napus) and its major belowground herbivore, the cabbage root fly (Delia radicum). We further assessed the influence of initial soil microbial diversity on these interactions. Different microbial diversities based on a common soil matrix were obtained through a removal-recolonization method. Root and rhizosphere sampling targeted different stages of the herbivore development corresponding to different perturbation intensities. Root bacterial communities were more affected by herbivory than some rhizosphere bacterial phyla and fungal communities, which seemed more resistant to this perturbation. Root herbivory enhanced the phylum of γ-Proteobacteria in the roots and rhizosphere, as well as the phylum of Firmicutes in the rhizosphere. Herbivory tended to decrease most root amino acids and sugars, and it increased trehalose, indolyl glucosinolates and sulfur. Higher abundances of four bacterial genera (Bacillus, Paenibacillus, Pseudomonas and Stenotrophomonas) were associated following herbivory to the increase of trehalose and some sulfur-containing compounds. Further research would help to identify the biological functions of the microbial genera impacted by plant infestation and their potential implications in plant defense.